Feminicidios y asesinatos de mujeres en los relatos periodísticos de El Heraldo 2016 y 2017: un ejercicio exploratorio de lectura distante (2021)
One of the manifestations of violence that affects the world the most is that against women and girls. Feminicides embody the most extreme gender-based violence. This exploratory work presents the results of a distant reading exercise of 224 press clippings accounting the murders of women, published in the regional newspaper El Heraldo between the years 2016 and 2017, with the aim of exposing the discourses constructed around feminicide and violence against women. The proposed methodology takes elements of discourse analysis using data obtained from computer-assisted reading and text analysis tools, such as Voyant Tools and Palladio. During the exploratory process, the need to address current issues in human studies became evident: access to sources and press archive management. The tools of text analysis allow for the establishment of connections and patterns in language use by providing visualizations that reveal information about the discursive constructions in the press regarding feminicide.